Analysis of Early Reading Ability of Children Aged 5–7 Years in Nuclear Family - Fortuna, Safira Bunga Cinta; Hanyfa, Nasywa Noor; Safitri, Maya Argilia Dian; Fauziyah, Zulfa Rihadah; Pertiwi, Adharina Dian (Jurnal Pendidikan Anak, 2025)
Early reading ability is a crucial component in shaping children’s language development in later stages of life. Various factors, such as mental readiness, social conditions, health status, educator competence, parental involvement in the learning process, and intelligence level, contribute to the formation of early literacy. Among these aspects, the role of parents is particularly decisive in children’s language development. This study focuses on language skills, particularly early reading ability, in children growing up in nuclear families. The research applied a quantitative method using survey techniques. A total of 34 children from nuclear families participated as respondents. Data were collected by distributing questionnaires compiled in Google Forms. Based on the analysis results, the average value of the research instrument reached 4.71 on a scale of 0 to 5, which is far from the low point (1), indicates that the early reading ability of children in nuclear families is in the excellent category.